Comparison of Mini-squats and Straight Leg Raises in Patients with Knee Osteoarthritis: A Randomized Controlled Clinical Trial - Arzu DAŞKAPAN; Bahar ANAFOROĞLU; Nihan ÖZÜNLÜ PEKYAVAŞ; Emine Handan TÜZÜN; Sacide NUR COŞAR; Metin KARATAŞ (Archives of Rheumatology, 2013)
Objectives: In this study, we aimed to compare the effects of the straight leg raise exercise (SLRE) and mini squat exercise (MSE) on pain intensity, performance, muscle strength, physical function and balance in patients with knee osteoarthritis (OA). Patients and methods: Forty female patients (mean age 59.93±10.61 years; range 30-65 years) who were admitted to Başkent University Hospital between February 2009 and February 2010 with bilateral knee OA were included in this randomized controlled double-blind clinical trial. The patients were assigned into two groups, including SLRE and MSE. Both exercise groups were scheduled for a threeweek program of five sessions per week. Both groups also received an electrotherapy program in each session. Knee pain using the visual analog scale (VAS), physical performance using Timed Up and Go (TUG) Test, isokinetic quadriceps and hamstring muscle strengths using Cybex II, static balance using SportKAT 3000, physical function using Knee Injury and Osteoarhtritis Outcome Score-Physical Function Short Form (KOOS-PS) were assessed at baseline, at treatment end, and one month after treatment end. Results: No significant difference was found in static balance testing parameters after exercise program (EP) (p=0.659) and during follow-up period (p=0.327) between the groups. There was no significant difference in KOOS-PS scores after EP (p=0.398) and during follow-up (p=0.201) between SLRE and MSE groups. There was no significant difference in VAS scores af ter EP (p=0.149), however significant difference was found during follow-up (p=0.030) between SLRE and MSE groups. Mini squat exercise group had significantly higher TUG scores and higher right knee extensor torque at 60°/sec (p=0.024), 90°/sec (p=0.003), 120°/sec (p=0.005) and 180°/sec (p=0.017) compared to the SLRE group at the end of EP. Conclusion: Further studies are required including long-term follow-up and the evaluation criteria of the effectiveness of SLRE and MSE after this period.